Assessing the driving forces for future housing design - Kutsal, Simge; Polatoglu, Cigdem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
The COVID-19 pandemic has underscored the imperative for housing to adapt to various factors, such as spatial, functional, climatic, and aesthetic considerations. The pandemic has transformed the dynamics between occupants and their living environments, influencing how different age groups interact with dwelling spaces, as well as impacting work, learning, healthcare access, and services. Urban life dynamics, especially in metropolitan areas, have undergone significant shifts due to social, cultural, technological, environmental, and economic factors. These changes, propelled by urbanization, demographic changes, evolving social structures, challenges in housing accessibility, and the rapid advancement of communication technologies, demand innovative approaches to housing design and programming. This study aims to identify future housing design trends and tendencies within this evolving context. Using a systematic literature review methodology, the study analyzed 87 articles published between 2010 and 2023, selected from digital databases according to predetermined criteria. Through meta-synthesis, STEEP analysis, and Shannon entropy assessments, the study identified 21 megatrends and 72 driving forces across the social, technological, environmental, economic, and political dimensions of housing design. The findings lay the groundwork for future housing innovations and sustainability, contributing to a wider discourse and enabling the generation of foresight model scenarios for housing design. Identifying these trends is crucial for creating functional, flexible, and sustainable living spaces that are suitable for the changing lifestyles and needs of individuals.
Keywords: Driving forces; housing; Shannon entropy; STEEP analysis; systematic review; Architecture